Reading and spelling skills in German third graders: Examining the role of student and context characteristics. (10th August 2015) - von Suchodoletz, Antje; Larsen, Ross A. A.; Gunzenhauser, Catherine; Fäsche, Anika
Abstract : Background: Educational processes and outcomes are influenced by a multitude of factors, including individual and contextual characteristics. Recently, studies have demonstrated that student and context characteristics may produce unique and cumulative effects on educational outcomes. Aims: The study aimed to investigate (1) the relative contribution of student, classroom, and school characteristics to reading fluency and orthographic spelling, (2) the relative contribution of specific predictors to reading fluency and orthographic spelling within the sets of student, classroom, and school characteristics, and (3) whether the contribution of student, classroom, and school characteristics differs for reading fluency and orthographic spelling. Sample: Participants were 789 German third‐grade students from 56 classrooms in 34 schools. Method: Students completed an intelligence test and a questionnaire assessing self‐control. Reading fluency and orthographic spelling performance were assessed using standardized achievement tests. Multilevel structural equation modelling was used to control for the hierarchical structure of educational data. Results and conclusion: Variances in students' reading and spelling skills were in large part explained by student characteristics (>90%). Classroom and school characteristics yielded little variance. Student‐level intelligence and self‐control were significantly related to reading fluency. For orthographic spelling, student‐level intelligence and self‐control, class‐average intelligence, and, at the school level, the socio‐economic status of the school's neighbourhood were significant predictors. Future research needs to investigate relevant classroom and school factors that may directly and indirectly relate to academic outcomes.